A periodized winter training block enhances anaerobic capacity in elite female rowers during 30-second maximal rowing - Liu, X.; Ding, Y.; Gong, Z.; Guo, P. (Frontiers in Physiology, 2025)
Objective: In competitive rowing, the winter training phase is a conventional periodized block focused on foundational physiological development through land-based strength and power training. The primary aim of this phase is to enhance athletes` force-generating capabilities and metabolic resilience. This study investigated the effects of such a 16-week periodized winter training block on anaerobic capacity and energy expenditure during a 30-s all-out rowing test in elite female rowers.